A Conscientious Review on Undergraduate Practicum Assessment Research Works of GAASC, Baitadi: Priorities, Gaps and Implications for Far Western Province, Nepal - Amgain, Lal Prasad; Dhakal, Deependra; Joshi, Liladhar (Journal of Agriculture and Forestry University, 2025)
The Far West Province (FWP), extending from the flatlands of Terai to high hills, is rich in untapped natural resources and offers a diverse agro-ecosystem with tremendous indigenous technical knowledge (ITKs). However, a vast number of bio-diversified resources are facing underutilization, while at the same time a handful are being over-exploited. Owing to a lack of proper documentation and disseminations of knowledge bases, the prosperity of the FWP is ruining to some extent. A systematic and rigorous review work was planned, executed and accomplished to appraise the undergraduate-practicum assessment (UPA) study conducted in the multi-disciplinary subjects of agriculture at Gokuleshwor Agriculture and Animal Science College (GAASC), Baitadi during 2014/15-2021/22 under Tribhuvan University. About 114 UPA theses accomplished by 359 agriculture graduates from the GAASC libraries were systematically arranged and categorized in chronological order based on the subject disciplines and themes, and recommended for their scale-up to the prosperity of farmers of the far western region in Nepal. The weighted term frequencies (TF-IDF) of the highest occurring terms appearing in the theses topics of B. Sc. Ag. students of GAASC, Baitadi during 2015- 2022 shows that crop specific research were more common in departments of Plant Pathology, Plant Breeding and Agronomy. The tracer study amongst the 237 graduate students of GAASC for the allotment of gazette (third class) Agriculture Service reported that an increasing tendency of agriculture graduates to continue with academia in spite of other career possibilities. The research review revealed that the maximum number of research were in the major production technologies in agronomical and vegetable crops and their marketing and value chain analysis followed by the control of insect pests and diseases both in farms and storage, suggesting to follow integrated pest management (IPM). The value-chain analysis study of the low volume high price commodity products like Jumli Marshi rice, Himali beans, temperate vegetable seeds, banana value addition and sugarcane enterprises and Yarsagumba (Ophiocordyceps sinensis) collection and selling are the potential avenues to boost the economic prosperity of the far western region of Nepal. Large scale adoption of new innovation like crop-weather and yield forecasting, introduction of farmers’ friendly agriculture machineries and value addition and marketing of the agriculture commodities tested in the province could be promoted in collaboration with the various agriculture related national and international organizations for harnessing congenial environment to the prosperity of Far West Region of Nepal.